Bioinformatic analysis of CHEK1 as a marker of glomerular epithelial cell injury in diabetic nephropathy: CHEK1 as a Marker of Diabetic Nephropathy Injury - Wang, Dan; Du, Yuejuan; Huang, Ran; Liu, Fang; Wang, Pu (Cellular and Molecular Biology, 2023)
Diabetic nephropathy (DN) is considered to be a kidney disease caused by diabetes. In recent years, the incidence of DN has been on the rise, which is also a major challenge in the treatment and prognosis of the disease. Therefore, the search for new biomarkers of DN is urgent and has important clinical significance for reducing the morbidity and mortality of DN. In this study, two datasets GSE1009 and GSE142153 were selected to extract expression profile-based data from DN glomerular samples, and 238 differentially expressed genes (DEGs) were screened. Then, through enrichment analysis, the biological function of DEGs involved in DN disease was preliminarily explored. Subsequently, the STRING website was used to construct a protein-protein interaction map (PPI) to find 10 key genes (CHEK1, ITGB3, COL4A2, COL4A5, COL4A3, COL4A4, CCNB2, CCNB1, TPX2, KIF11), Which play an important role in the progression of DN disease and are closely related to other genes. CHEK1 was the focus of this study, and the expression level of CHEK1 in glomerular epithelial cell models was verified by qRT-PCR. Our results suggest that CHEK1 is a potential biomarker of the degree of damage to DN glomerular epithelial cells.